2000
DOI: 10.1034/j.1600-0714.2000.290903.x
|View full text |Cite
|
Sign up to set email alerts
|

First hints for a correlation between amplification of the Int‐2 gene and infection with human papillomavirus in head and neck squamous cell carcinomas

Abstract: Infection with human papillomavirus (HPV) and alterations in certain genes have frequently been proposed as mechanisms in the pathogenesis of head and neck squamous cell carcinoma (HNSCC). Here, we investigated 47 HNSCC for the presence of HPV and, by fluorescence in situ hybridisation, for amplification of Int-2 and Hst-1 in the search for a possible correlation. The highest frequency of HPV infection was found in hypopharyngeal carcinomas, while amplification of Int-2 or Hst-1 was distributed more equally am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…All primer sequences are available from the authors on request. The reactions were performed as described before with the following annealing temperatures: 50°C (HPV31, HPV52), 55°C (MY09, MY11, HPV18, HPV33, HPV45, HPV51), and 60°C (HPV6/11, HPV16) [16]. The products were analyzed by electrophoresis on polyacrylamide gels and detected by silver staining.…”
Section: Methodsmentioning
confidence: 99%
“…All primer sequences are available from the authors on request. The reactions were performed as described before with the following annealing temperatures: 50°C (HPV31, HPV52), 55°C (MY09, MY11, HPV18, HPV33, HPV45, HPV51), and 60°C (HPV6/11, HPV16) [16]. The products were analyzed by electrophoresis on polyacrylamide gels and detected by silver staining.…”
Section: Methodsmentioning
confidence: 99%
“…Despite using the most sensitive method (PCR), we still observed a large variation in HPV detection rates, which can be explained by the relationship between results and sample sizes. In fact, the Kleist et al study observed an 80% positivity among 5 samples, while Ribeiro et al only detected HPV in 3.8% of cases among 78 tumors (Kleist et al, 2000;Ribeiro et al, 2011).…”
Section: Human Papillomavirus and Related Diseases -From Bench To Bedmentioning
confidence: 98%
“…Based on the literature, we observed a prevalence ranging from 0% to 82% (Ernoux et al, 2011;Hafkamp et al, 2003;Ringström et al, 2002). In fact, some authors failed to show prevalence higher than 10% (Gillison et al, 2000;Hafkamp et al, 2003;Ribeiro et al, 2011;Ringström et al, 2002;Stremlau et al, 1987), whereas others found prevalence greater than 50% (Arndt et al, 1992;Ernoux et al, 2011;Kleist et al, 2000;Koskinen et al, 2003;Tyan et al, 1993). Recently, we examined the presence of HPV DNA in a series of 75 patients with stage IV hypopharyngeal SCC (Ernoux et al, 2011).…”
Section: Incidence In Hypopharyngeal Tumorsmentioning
confidence: 99%
“…Despite using the most sensitive method (PCR), we still observed a large variation in HPV detection rates, which can be explained by the relationship between results and sample sizes. In fact, the Kleist et al study observed an 80% positivity among 5 samples, while Ribeiro et al only detected HPV in 3.8% of cases among 78 tumors (Kleist et al, 2000;.…”
Section: Incidence In Hypopharyngeal Tumorsmentioning
confidence: 99%
“…Based on the literature, we observed a prevalence ranging from 0% to 82% (Ernoux et al, 2011;Hafkamp et al, 2003;. In fact, some authors failed to show prevalence higher than 10% Hafkamp et al, 2003;Stremlau et al, 1987), whereas others found prevalence greater than 50% (Arndt et al, 1992;Ernoux et al, 2011;Kleist et al, 2000;Koskinen et al, 2003;. Recently, we examined the presence of HPV DNA in a series of 75 patients with stage IV hypopharyngeal SCC (Ernoux et al, 2011).…”
Section: Incidence In Hypopharyngeal Tumorsmentioning
confidence: 99%